Optimizing the Performance of the Driving Permit Service Unit through the LinkAja Application for Excellent Service at the Jepara Police - Ilham Siplizand (Advances in Police Science Research Journal, 2022)
The Jepara Police station’s Driver license Service Unit or known as Satpas 1438, in collaboration with Telkomsel made an application of “Link Aja” that facilitated the public in paying The payment of the driver’s license. With the Link Aja application, it is hoped that it can help the community because it is easier and more time efficient. It is so that people do not need to go to banks and instead just use the Link Aja application. This facility is expected to be able to provide excellent service and be able to increase public confidence in the National Police. Driver license payment based on the application, namely through the Link Aja Application has been carried out for 2 years since its inception in 2020 until 2022, however, the procedure for payment through Link Aja Polres Jepara was only issued on January 5, 2022 and the application has been implemented for 3 years starting from 2019. Until now there should be many benefits and conveniences provided by the innovation so that it becomes one of the main services provided to the community in the Driver’s license payment process. The method used in this research is a qualitative approach. It is conducted with the implementation of driver license service activities by the Jepara Police driver license Service Unit which is based on the driver license payment procedure using Link Aja in 2022. The research starts from the preparation, organizing, implementation, supervision, analysis and evaluation stages have been carried out. It has been found however, in each part of the management there are still shortcomings that have an impact on the purpose and utilization of the service delivery using Link Aja itself. Due to that, efforts are made in improving the performance of the Jepara Police station’s driver license Service Unit in the form of optimizing the performance of the Jepara Police station’s driver license Service Unit through the Link Aja application for excellent service at the Jepara Police station.